The Irish Cultural Borderscape - McCall, Cathal (Irish Journal of Arts Management and Cultural Policy, 2019)
This paper discusses the Irish cultural borderscape, or border region, as the epicentre for the development of cross-border cultural policy. Where PEACE projects have funded efforts that encourage the search for commonalities and a respect for difference, the paper posits that the Brexit process reasserts the differences that the Irish borderscape has been challenging for twenty years.